Gender Differences in the Association between Marijuana and Menthol Cigarette Use among African American Adult Cigarette Smokers. (1st May 2020) - Montgomery, LaTrice; Webb Hooper, Monica
Abstract: Introduction: Despite the strong relationship between marijuana and tobacco use, especially among African American individuals and males, very few studies have examined the association between marijuana and menthol cigarette use. This study was designed to identify the prevalence of past month, past year and lifetime marijuana use and marijuana dependence among menthol and non-menthol cigarette smokers, as well as the association between marijuana and menthol cigarette use among African American female and male cigarette smokers. Methods: Data were drawn from 1, 173 African American adult cigarette smokers in the 2017 National Survey on Drug Use and Health. Results: Overall, 8.8%, 13.9% and 44.7% of African American menthol and non-menthol cigarette smokers reported past month, past year and lifetime marijuana use, respectively. Weighted multivariable logistic regression models revealed a significant interaction between gender and past month marijuana use on menthol cigarette use ( AOR  = 1.49, 95% CI: 1.21-2.42, p < .05). Past month marijuana use was associated with an increased odds of past month menthol cigarette use (relative to non-menthol cigarette use) among females, but a decreased odds of past of past month menthol cigarette use among males. Conclusions: When stratified by gender, marijuana use is differentially related to menthol cigarette use among African American adults. Given the prevalence of menthol cigarette use among this population, it is important to examine factors such as marijuana use that could be targeted in prevention and treatment interventions for African Americans, especially females, who are at risk for smoking or are currently smoking menthol cigarettes. Implications: This study found that marijuana use was associated with an increased odds of menthol cigarette use among African American females, while marijuana use was associated with a decreased odds of menthol cigarette use among their male counterparts. The impact of marijuana use on menthol cigarette smoking differs among females and males, highlighting the need for gender-tailored interventions that target marijuana use among African American individuals, especially females, who are at risk for smoking or are currently smoking menthol cigarettes.